Kaedah Pemikiran Kritis al-Dihlawi terhadap Perbahasan al-Sa’adah (Kebahagiaan) dalam Karya Hujjah Allah al-Balighah: Al-Dihlawi’s Critical Thinking Method on al-Sa’adah (Happiness) Debate in the Manuscript of Hujjah Allah al-Balighah (KEMANUSIAAN The Asian Journal of Humanities, 2023)
During this era, the world is evolving at such a rapid pace that there is uncertainty and confusion. The idea of modernity embodied by the West has spawned thoughts that contradict Islamic sharia thus rejecting the authority of the Quran and Sunnah as the main source of reference for Muslims. In today’s technological rapidity, Islam is seen as a backward religion and its teachings need to be adapted to the modern lifestyle thus damaging the faith of the Muslims themselves. This study aimed to analyse al-Dihlawi’s critical thinking method through the debate of al-sa’adah (happiness) in the book titled “Hujjah Allah al-Balighah”. This study employed a qualitative approach. The highlights of in-depth readings were derived primarily from the book of Hujjah Allah al-Balighah. The first step was to translate the text, followed by a content analysis method to extract the concept of happiness discussed in the book and explore it in the context of the critical thinking method in al-Dihlawi’s view. This study’s results found that al-Dihlawi’s critical thinking method was used in debating al-sa’adah in five methods: question and answer thinking, rational thinking, scientific thinking, Sufi thinking and rabbani thinking. If Muslims appreciate and apply al-Dihlawi’s critical thinking method, they could strengthen their mind and direct their thinking toward pursuing happiness in this world and the hereafter. Happiness begins when the human mind can control lust and reject anything that is against revelation. Via critical thinking, humans can distinguish between right and wrong through a guide to revelation. When a person can control lust and has a high level of obedience and carry out their obedience to Allah’s commands with a full sense of responsibility as his servant, then he can draw closer to Allah SWT and acquire His blessings.Era ini menyaksikan dunia yang berkembang dengan begitu pantas sehingga berlaku ketidakpastian dan kecelaruan pemikiran. Gagasan kemodenan yang dicanangkan oleh Barat telah melahirkan pemikiran-pemikiran yang bertentangan dengan akidah Islam sehingga menolak keautoritian al-Quran dan Sunah. Dalam kepesatan teknologi kini juga, umat Islam dilihat perlu menyesuaikan kehidupan mereka dengan gaya hidup moden walaupun bersalahan dengan ajaran Islam. Kajian ini bertujuan untuk menganalisis kaedah pemikiran kritis al-Dihlawi berdasarkan perbahasan al-sa’adah (kebahagiaan) dalam kitab Hujjah Allah al-Balighah. Kajian ini menggunakan kaedah kualitatif. Sorotan pembacaan secara mendalam telah dilakukan terhadap kitab Hujjah Allah al-Balighah sebagai sumber utama. Penterjemahan teks merupakan langkah pertama diikuti kaedah analisis kandungan bagi mengekstrak konsep kebahagiaan yang dikupas oleh al-Dihlawi dalam konteks kaedah pemikiran kritis. Hasil analisis mendapati terdapat lima kaedah pemikiran kritis al-Dihlawi yang digunakan dalam membahaskan al-sa’adah, iaitu pemikiran soal jawab, rasional, saintifik, kesufian dan rabbani. Dengan kaedah ini, umat Islam dapat memantapkan minda dan pemikiran dalam mencapai kebahagiaan hidup di dunia dan akhirat. Kebahagiaan bermula ketika akal manusia dapat menguasai nafsu dan menolak perkara bertentangan dengan wahyu. Pemikiran kritis mengupayakan manusia untuk membezakan antara yang benar dengan yang batil melalui panduan wahyu. Ketika seseorang telah menguasai nafsunya dan memiliki sifat ketaatan yang tinggi, maka dia dapat mendekatkan diri kepada Allah SWT dan memperoleh keberkatan-Nya.